Social determinants of ambulatory care sensitive conditions: a qualitative meta-synthesis based on patient perspectives - Chen, Hsueh-Fen; Lin, Hung-Ru (Frontiers in Public Health, 2023)
Background Hospitalizations or emergency department (ED) visits due to ambulatory care-sensitive conditions (ACSC) are preventable but cost billions in modern countries. The objective of the study is to use a meta-synthesis approach based on patients' narratives from qualitative studies to reveal why individuals are at risk of ACSC hospitalizations or ED visits. Methods PubMed, Embase, Cochrane Library, and Web of Science databases were utilized to identify qualified qualitative studies. The Preferred Reporting Items for Systematic Review and Meta-Analysis were used for reporting the review. The thematic synthesis was used to analyze the data. Results Among 324 qualified studies, nine qualitative studies comprising 167 unique individual patients were selected based on the inclusion/exclusion criteria. Through the meta-synthesis, we identified the core theme, four major themes, and the corresponding subthemes. Poor disease management, the core theme, turns individuals at risk of ACSC hospitalizations or ED visits. The four major themes contribute to poor disease management, including difficulties in approaching health services, non-compliance with medications, difficulties in managing the disease at home, and poor relationships with providers. Each major theme comprised 2–4 subthemes. The most cited subthemes are relative to upstream social determinants, such as financial constraints, inaccessible health care, low health literacy, psychosocial or cognitive constraints. Conclusion Without addressing upstream social determinants, socially vulnerable patients are unlikely to manage their disease well at home even though they know how to do it and are willing to do it. Trial registration National Library of Medicine, with ClinicalTrials.gov, Identifier: NCT05456906. https://clinicaltrials.gov/ct2/show/NCT05456906.